1997
DOI: 10.1002/(sici)1096-8628(19970531)74:3<324::aid-ajmg15>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CAG repeats in the SCA1 and B37 genes in schizophrenic and bipolar I disorder patients: Tentative association between B37 and schizophrenia

Abstract: We have genotyped unrelated French Alsatian schizophrenic and bipolar I disorder (BPD) patients and matched controls for the polymorphic CAG repeats within the genes for spinocerebellar ataxia type 1 (SCA1) and dentatorubral-pallidoluysian atrophy (B37), in order to test their possible involvement in these disorders. No alleles with abnormally expanded repeats were found in either gene in patients and controls. Differences in allele and genotype frequencies for the SCA1 CAG repeat between patients and controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As several studies have suggested an association between large CAG repeats and severe mental illnesses using the repeat expansion detection (RED) method, 15-17 the result is not unequivocal 18 and the candidate genes for schizophrenia remain unidentified. 19,20 The results of our study, nevertheless, exclude the possible involvement of the CAG triplet-containing gene, KCNN3, in the pathogenesis of schizophrenia in our population.…”
mentioning
confidence: 39%
“…As several studies have suggested an association between large CAG repeats and severe mental illnesses using the repeat expansion detection (RED) method, 15-17 the result is not unequivocal 18 and the candidate genes for schizophrenia remain unidentified. 19,20 The results of our study, nevertheless, exclude the possible involvement of the CAG triplet-containing gene, KCNN3, in the pathogenesis of schizophrenia in our population.…”
mentioning
confidence: 39%
“…All patients and controls described here have previously been used in other published studies. 13,18 European patients: Unrelated patients of French or Alsatian ancestry meeting DSM-IV criteria for schizophrenia or BPD-I were genotyped; Mediterranean Caucasians, Asians, and Africans were excluded. Patients were examined with an unstructured clinical interview and also with a structured clinical interview (SADSLifetime Version, 35 final diagnoses being made by a consensus of two psychiatrists.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…[9][10][11][12] Despite extensive studies, the precise gene(s) containing the longer CAG alleles associated with neuropsychiatric disorders remain unidentified. [13][14][15] In this study, we describe a novel potassium channel gene, hSKCa3, involved in neuronal excitability, that shows the predicted signifi- ) is derived from a combination of the published AAD14 cDNA, our human genomic and brain cDNA sequences, and the human EST AA285078; rSKCa3 is derived from the published cDNA sequence. The putative transmembrane segments and pore region are bracketed, and the two polyglutamine arrays are shown in bold and bracketed.…”
mentioning
confidence: 99%
See 2 more Smart Citations